The experiences of Māori social workers in schools working alongside teachers to support tamariki : a thesis presented in partial fulfilment of the requirements of the Master of Social Work at Massey University, New Zealand - Pirika, Terry Gipsy (Massey University, 2021)
This thesis critically engages with Māori Social Workers in Schools to develop a more in-depth understanding of their practice methods and the experiences of working alongside teachers to support tamariki. Social workers in Aotearoa New Zealand have been part of the profession’s historical commitment to assist people from within their systems and environments. Many of today's schools of social work practice are groups of professionals who align themselves with a particular position in terms of building social work knowledge, with a focus on treating children's emotional and relational struggles, which are exacerbated by a deprivation in health, finances, and education. All of which have been linked to affecting a child’s school performance. The number of children being affected continues to rise, alongside the gradual decline in resources. In all social, economic and health statistics, Māori are substantially overrepresented. For the most part, this has been primarily due to the colonial disadvantages of western models of policies and practices implemented throughout Aotearoa New Zealand education. In order to cope with this changing landscape, school social workers have needed to develop new ways of reaching out to more children across all areas of the school environment. To do so, increasingly more social work practitioners have adopted ways of practice that are informed by Māori principles and values. For example, the incorporation of school staff members and social workers in attempts to build a stronger school system, as well as act as a liaison between various organisational services, allowing for greater utilisation and collaboration of expertise that can be significant in crafting ecological change. Kaupapa Māori research concepts were used to underpin this research thesis. A qualitative method of study was employed, and semi-structured interviews were conducted with research kaimahi. Six Māori social workers in schools were interviewed kanohi ki te kanohi (face-to-face) and guided by a holistic model of practice, which allowed the voices of kaimahi to be heard, while also expressing their opinions in detail. The review of the literature shows that whakawhanaungatanga is seen by Māori social workers as significant in their mahi as it ensures the practice in a way that promotes their work with teachers, tamariki, and whānau. One key finding evident within each kaimahi practice were values and beliefs that they drew from their upbringing and lived experiences, according to their worldviews. Another key result was the concept of taking care of the 'self'; in other words, being open to receiving good whānau and mahi support, speaking about the challenges and obstacles, obtain good cultural and peer supervision, which in turn aided in the development and growth for all kaimahi involved in this study. Overall, this research highlights the importance of the SWiS role, the collaboration with schools, and the flexibility that the role offers for SWiS to implement their creative skills in the delivery of programmes.
Keywords: 451126 Ngā mahi tauwhiro me te tika pāpori o te Māori (Māori social work and social justice)